Highland cropland expansion and forest loss in Southeast Asia in the twenty-first century - Zeng, Zhenzhong; Estes, Lyndon; Ziegler, Alan D; Chen, Anping; Searchinger, Timothy; Hua, Fangyuan; Guan, Kaiyu; Jintrawet, Attachai; Wood, Eric F (Nature geoscience, 2018)
Southeast Asia is a hotspot of tropical deforestation for agriculture. Most of the deforestation is thought to occur in lowland forests, whereas the region’s mountainous highlands undergo very limited deforestation. However, regional reports of cropland expansion in some highland areas suggest that this assumption is inaccurate. Here we investigate patterns of forest change and cropland expansion in the region for the twenty-first century, based on multiple streams of state-of-the-art satellite imagery. We find large increases in cultivated areas that have not been documented or projected. Many of these cultivated areas have evolved from forests that vary in health and status, including primary and protected forests, or from recovering lands that were on a trajectory to become secondary forests. These areas all have different biophysical features than croplands. We estimate that an area of 82 billion m2 has been developed into croplands in the Southeast Asian highlands. Some portion of this land-use change is probably attributable to agricultural intensification on formerly swidden agriculture lands; however, a substantial proportion is from new forest loss. Our findings are in marked contrast with projections of land-cover trends that currently inform the prediction of future climate change, terrestrial carbon storage, biomass, biodiversity, and land degradation.